2010
DOI: 10.4103/0972-5229.74170
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury after trauma: Prevalence, clinical characteristics and RIFLE classification

Abstract: Background:Acute kidney injury (AKI) is an uncommon but serious complication after trauma. The objective of this study was to evaluate the prevalence, clinical characteristics and outcome of AKI after trauma.Patients and Methods:This was a retrospective study performed from January 2006 to January 2008 in an emergency specialized hospital in Fortaleza city, northeast of Brazil. All patients with AKI admitted in the study period were included. Prevalence of AKI, clinical characteristics and outcome were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 56 publications
3
47
0
4
Order By: Relevance
“…These findings contrast with other forms of trauma-associated AKI, where authors have reported mortality rates ranging from 28% to 100%. [11][12][13] Other studies examining mortality from all causes of rhabdomyolysis report rates of 5 -24%. [6,8,14] …”
Section: Discussionmentioning
confidence: 99%
“…These findings contrast with other forms of trauma-associated AKI, where authors have reported mortality rates ranging from 28% to 100%. [11][12][13] Other studies examining mortality from all causes of rhabdomyolysis report rates of 5 -24%. [6,8,14] …”
Section: Discussionmentioning
confidence: 99%
“…Understanding the onset characteristics of AKI and the risk factors associated with its prognosis will improve the clinical prevention and treatment of AKI. Previous epidemiological studies on AKI often concentrate on single disease or intensive care units [2,3,4]; moreover, the applied AKI standards are different [5,6,7] and not all hospitalized patients are covered and so the sampling error exists; some studies only observe the hospitalized AKI patients whose serum creatinine (Scr) exceeds the normal range, while the patients at early stage whose Scr obviously increases but is still within the normal range [8] are ignored.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, colloids resulted in an increase in acute kidney injury among patients with sepsis; conversely, they were protective against such injury in patients with traumatic injuries. This is scientifically plausible as trauma is characterized by volume loss leading to hypotension and renal ischaemia, resulting in acute kidney injury. Administration of colloid in injured patients rapidly increases systemic BP and improves renal perfusion.…”
Section: Discussionmentioning
confidence: 99%